Active defense ebook - Eason, Lynette (Danger Never Sleeps, 2021)
In the theater of war in Afghanistan, trauma surgeon Heather Fontaine was used to being in control. Now back home, life spins off its axis when she becomes the target of a stalker. Can security expert Travis Walker protect her?